2012
DOI: 10.1002/jcp.24062
|View full text |Cite
|
Sign up to set email alerts
|

Src modulates contractile vascular smooth muscle function via regulation of focal adhesions

Abstract: Src is a known regulator of focal adhesion turnover in migrating cells; but, in contrast, Src is generally assumed to play little role in differentiated, contractile vascular smooth muscle (dVSM). The goal of the present study was to determine if Src-family kinases regulate focal adhesion proteins and how this might affect contractility of non-proliferative vascular smooth muscle. We demonstrate here, through the use of phosphotyrosine screening, deconvolution microscopy imaging, and differential centrifugatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
64
2
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(74 citation statements)
references
References 36 publications
5
64
2
3
Order By: Relevance
“…Not all FA-associated proteins exhibit the same redistribution pattern. It has previously been reported that CAS, a scaffolding protein and Src, a tyrosine kinase, are signaling molecules associated with dVSM FAs and that they redistribute to the membrane from the cytoskeletal fraction (37). We have confirmed those data and demonstrate in Fig.…”
Section: Pe Triggers Redistribution Of Zyxin Vasp Paxillin and Metsupporting
confidence: 89%
See 1 more Smart Citation
“…Not all FA-associated proteins exhibit the same redistribution pattern. It has previously been reported that CAS, a scaffolding protein and Src, a tyrosine kinase, are signaling molecules associated with dVSM FAs and that they redistribute to the membrane from the cytoskeletal fraction (37). We have confirmed those data and demonstrate in Fig.…”
Section: Pe Triggers Redistribution Of Zyxin Vasp Paxillin and Metsupporting
confidence: 89%
“…In airway smooth muscle, agonist-induced vinculin (27), paxillin (53), FA kinase (FAK), talin (42), and ␣-actinin (64) redistribution occurs and is necessary for active tension development with cholinergic agonists. In dVSM, VASP shifts from the soluble fraction to the insoluble fraction in response to a phorbol ester (34), and Src and p130 Crk-associated substrate (CAS) redistribute between insoluble and soluble fractions in response to an ␣-agonist (37). Finally, norepinephrine-or endothelin-induced stimulation of small mesenteric arteries causes redistribution of paxillin from a soluble fraction to an insoluble fraction (41).…”
mentioning
confidence: 99%
“…We combined the validated and predicted target list and performed a pathway enrichment analysis using the Kyoto Encyclopedia of Genes and Genome database. Several pathways with a clear involvement in vascular physiology were found to be significantly enriched, such as the mitogenactivated protein kinase (MAPK) signaling pathway, 34 focal adhesion, 35 insulin signaling pathway, 36 adherens junctions, 37 transforming growth factor (TGF)-β signaling pathway, 38 and the Wnt signaling pathway 39 ( Table V in …”
Section: Pathway Enrichment Analysismentioning
confidence: 99%
“…In doi: 10.7243/2055-0898-2-2 this light the GTPases Rho, Rac and cdc42 play critical roles: Rho mediates cell contractility, Rac regulates protrusions of lamellipodia and filopodia and cdc42 regulates directionality [3]. Other focal adhesion proteins such as focal adhesion kinase (FAK), Src and paxillin (PAX) also play key roles in this process [2,4]. Focal adhesion kinase is an intracellular protein tyrosine kinase (PTK) that is recruited to and activated at focal adhesion (FA) sites and that acts downstream of multiple ECM components [5].…”
Section: Introductionmentioning
confidence: 99%